Development of New Leishmanicidal Compounds via Bioconjugation of Antimicrobial Peptides and Antileishmanial Guanidines - Costa, Natalia C. S. [UNESP]; dos Anjos, Luana Ribeiro [UNESP]; de Souza, João Victor Marcelino [UNESP]; Brasil, Maria Carolina Oliveira de Arruda [UNESP]; Moreira, Vitor Partite [UNESP]; Graminha, Marcia A. S. [UNESP]; Lubec, Gert; Gonzalez, Eduardo Rene P. [UNESP]; Cilli, Eduardo Maffud [UNESP] (American Chemical Society (ACS), 2023)
Leishmaniasis refers to a collection of diseases caused by protozoa from the Leishmania genus. These diseases, along with other parasitic afflictions, pose a significant public health issue, particularly given the escalating number of at-risk patients. This group includes immunocompromised individuals and those residing in impoverished conditions. The treatment of leishmaniasis is crucial, particularly in light of the mortality rate associated with nontreatment, which stands at 20-30,000 deaths per year globally. However, the therapeutic options currently available are limited, often ineffective, and potentially toxic. Consequently, the pursuit of new therapeutic alternatives is warranted. This study aims to design, synthesize, and evaluate the leishmanicidal activity of antimicrobial peptides functionalized with guanidine compounds and identify those with enhanced potency and selectivity against the parasite. Accordingly, three bioconjugates were obtained by using the solid-phase peptide synthesis protocol. Each proved to be more potent against intracellular amastigotes than their respective peptide or guanidine compounds alone and demonstrated higher selectivity to the parasites than to the host cells. Thus, the conjugation strategy employed with these compounds effectively contributes to the development of new molecules with leishmanicidal activity.